Սարգիս Վ. Կունտ - Հ. Ն. Ակինեան (Տպարան Սրբոյ Յակոբեանց)
Եւ իր մեկնողական երկասիրութիւնները
Keywords: The Bible; Auxiliary Sciences of History; Language and Literature; Biography; Literature; Literary History